Penerapan Model TPACK pada Pembelajaran Pendidikan Agama Islam dan Budi Pekerti untuk Meningkatkan Hasil Belajar Siswa Kelas X DPIB SMKN 2 Kota Palopo - Sabir, Nurhikma; Amin, Muh. Agil; Yusuf, Munir (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this research is to explore how the implementation process is carried out within the scope of the study. and impact of applying the TPACK-based video learning model regarding its influence on students’ academic performance in the Islamic Religious Education and Character subject for Grade X DPIB students at SMKN 2 Palopo. The study applied a Classroom Action Research, approach implemented across two successive cycles with a cohort of 19 students. Data were obtained through structured observations, test instruments, and supporting documentation, then processed through systematic analytical techniques. both qualitatiive and quantiative approaches. the finding’s indicate a notable increase in student activity and academic performance following the application of the TPACK model. Student activity scores increased from 39 (81.25%) from the initial cicle to 43 (89.58%) during the subsequent cycle, whereas the mean academic score improved from 73.13 (37.5% mastery) in the pre-cycle to 90 (93.75% mastery) during the subsequent cycle. Therefore, the implementation of thee TPACK-based video learning model proved effective in enhancing student engagement and achievement in Islamic Religious Education and can serve as an innovative strategy to address learning challenges in the digital era.